Relationship between Patient Profile and Quality of Life for Palliative Cancer Patients at Dr. Mohammad Hoesin General Hospital, Palembang - Kumaladewi, Yuliana; Rahmiati (Jurnal RSMH Palembang, 2023)
Relationship between Patient Profile and Quality of Life for Palliative Cancer Patients at Dr. Mohammad Hoesin General Hospital, Palembang. Cancer treatment affects all aspects of the patient's life, both the physical and psychological condition of the patient. Measurement of quality of life is important to do to improve treatment or rehabilitation, medical decision making, and facilitate communication between health workers and palliative cancer patients. This research is an analytic descriptive study using a cross-sectional design with a quantitative approach. The purpose of this study was to determine the relationship between cancer palliative patient profile and quality of life. The instrument for assessing the quality of life is the WHOQOL-BREF instrument. The research sample was 64 adult patients with palliative cancer who were treated in inpatient ward. The majority of the sample is female (79,9%), aged over 46 years old (54,7%), married (85, 9%) and ongoing chemotherapy (78,1%). Based on the results of this study, the quality of life of 60 patients was in a good category (93.8%) and the remaining had a moderate quality of life (6.3%). The majority of poor quality of life occur in domain 2 (psychological) as much as 68.8% and domain 4 (environment) as much as 59.4%. Type of therapy has a significant relationship with quality of life with p value = 0.006. The patient profile (education and cancer stage) is significantly related to the psychological domain and the cancer stage profile is related to the environmental domain. The conclusion of this study is that the type of therapy is related to the patient's quality of life. The quality of life of cancer palliative patients needs to be considered by nurses, especially related to the psychological domain and the environmental domain.